2012
DOI: 10.5014/ajot.2012.003244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vision Impairment on Intensity of Occupational Therapy Utilization and Outcomes in Subacute Rehabilitation

Abstract: OBJECTIVE. To examine whether vision impairment is a predictor of intensity of occupational therapy utilization and outcomes in a sample of older adults ages ≥55 receiving subacute rehabilitation in a long-term care setting. METHOD. Data for this cohort study were collected by means of structured, in-person interviews with 100 older adult rehabilitation patients at admission to a subacute unit in a long-term care facility and by medical chart review after discharge. RESULTS. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…One challenge, however, is that older adults generally reported a lower incidence of vision problems in questionnaires or screening questions than was found when the vision loss was identified by testing. Older adults reported vision loss at a rate of 14% in the study by Simonsick et al (1999) and 21% in the Demura et al (2014) study, whereas testing of this age group showed significantly decreased visual skills in approximately 25% (Tiedemann et al, 2005;Roche et al, 2014) to 32% of similar populations (Cimarolli et al, 2012). The Perlmutter et al (2010) study noted that only 15% of their subjects self-reported limited vision; however, 40% of the same subjects tested as having significant vision loss.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…One challenge, however, is that older adults generally reported a lower incidence of vision problems in questionnaires or screening questions than was found when the vision loss was identified by testing. Older adults reported vision loss at a rate of 14% in the study by Simonsick et al (1999) and 21% in the Demura et al (2014) study, whereas testing of this age group showed significantly decreased visual skills in approximately 25% (Tiedemann et al, 2005;Roche et al, 2014) to 32% of similar populations (Cimarolli et al, 2012). The Perlmutter et al (2010) study noted that only 15% of their subjects self-reported limited vision; however, 40% of the same subjects tested as having significant vision loss.…”
Section: Discussionmentioning
confidence: 92%
“…Other questionnaires were designed to screen for any loss in visual skills, including those associated with age-related eye conditions. The Vision Screening Questionnaire for Older People (Horowitz, Teresi, & Cassels, 1991) was used for self-report of vision loss prior to screening of vision skills in the study by Cimarolli et al (2012). The Visual Impairment Screening Questionnaire was translated and adapted from the Vision Screening Questionnaire by Horowitz et al (1991) and was used by home health care providers to recognize suspected vision loss as part of an initiative to identify individuals at risk of falls (McGraw, Dery, & Wittich, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of vision impairment in an older adult client receiving rehabilitation may affect the outcome of the occupational therapy intervention. Cimarolli, Morse, Horowitz, and Reinhardt (2012) reported that vision impairment negatively affected the use of occupational therapy services and predicted higher functional dependence at discharge in older adults in a subacute rehabilitation setting. Similarly, vision impairment was shown to reduce the effectiveness of rehabilitation after a hip fracture (Lieberman, Friger, & Lieberman, 2004).…”
mentioning
confidence: 99%